Mid- to Late-Holocene branched GDGT-based air temperatures from a crater lake in Cameroon (Central Africa) - Guillemette Ménot; Salomé Ansanay-Alex; Valérie F. Schwab; Gilbert Todou; Olivier Séné; Jean-Michel Onana; Gerd Gleixner; Dirk Sachse; Yannick Garcin (Organic Geochemistry, 2025)

Bioavailable carbon additions to soil promote free-living nitrogen fixation and microbial biomass growth with N-free lipids - Georg Dittmann; Su Ding; Ellen C. Hopmans; Simon A. Schröter; Alice M. Orme; Erika Kothe; Markus Lange; Gerd Gleixner (Soil Biology and Biochemistry, 2025)

Plant diversity and community age stabilize ecosystem multifunctionality - Peter Dietrich; Anne Ebeling; Sebastian T. Meyer; Ana Elizabeth Bonato Asato; Maximilian Bröcher; Gerd Gleixner; Yuanyuan Huang; Christiane Roscher; Bernhard Schmid; Anja Vogel; Nico Eisenhauer (Global Change Biology, 2024)
It is well known that biodiversity positively affects ecosystem functioning, leading to enhanced ecosystem stability. However, this knowledge is mainly based on analyses using single ecosystem functions, while studies focusing on the stability of ecosystem multifunctionality (EMF) are rare. Taking advantage of a long‐term grassland biodiversity experiment, we studied the effect of plant diversity (1–60 species) on EMF over 5 years, its temporal stability, as well as multifunctional resistance and resilience to a 2‐year drought event. Using split‐plot treatments, we further tested whether a shared history of plants and soil influences the studied relationships. We calculated EMF based on functions related to plants and higher‐trophic levels. Plant diversity enhanced EMF in all studied years, and this effect strengthened over the study period. Moreover, plant diversity increased the temporal stability of EMF and fostered resistance to reoccurring drought events. Old plant communities with shared plant and soil history showed a stronger plant diversity–multifunctionality relationship and higher temporal stability of EMF than younger communities without shared histories. Our results highlight the importance of old and biodiverse plant communities for EMF and its stability to extreme climate events in a world increasingly threatened by global change.

Stability and carbon uptake of the soil microbial community is determined by differences between rhizosphere and bulk soil - Markus Lange; Mina Azizi-Rad; Georg Dittmann; Dan Frederik Lange; Alice May Orme; Simon Andreas Schroeter; Carsten Simon; Gerd Gleixner (Soil Biology and Biochemistry, 2024)

Increased soil carbon storage through plant diversity strengthens with time and extends into the subsoil - Markus Lange; Nico Eisenhauer; Hongmei Chen; Gerd Gleixner (Global Change Biology, 2023)
Soils are important for ecosystem functioning and service provisioning. Soil communities and their functions, in turn, are strongly promoted by plant diversity, and such positive effects strengthen with time. However, plant diversity effects on soil organic matter have mostly been investigated in the topsoil, and there are only very few long‐term studies. Thus, it remains unclear if plant diversity effects strengthen with time and to which depth these effects extend. Here, we repeatedly sampled soil to 1 m depth in a long‐term grassland biodiversity experiment. We investigated how plant diversity impacted soil organic carbon and nitrogen concentrations and stocks and their stable isotopes 13 C and 15 N, as well as how these effects changed after 5, 10, and 14 years. We found that higher plant diversity increased carbon and nitrogen storage in the topsoil since the establishment of the experiment. Stable isotopes revealed that these increases were associated with new plant‐derived inputs, resulting in less processed and less decomposed soil organic matter. In subsoils, mainly the presence of specific plant functional groups drove organic matter dynamics. For example, the presence of deep‐rooting tall herbs decreased carbon concentrations, most probably through stimulating soil organic matter decomposition. Moreover, plant diversity effects on soil organic matter became stronger in topsoil over time and reached subsoil layers, while the effects of specific plant functional groups in subsoil progressively diminished over time. Our results indicate that after changing the soil system the pathways of organic matter transfer to the subsoil need time to establish. In our grassland system, organic matter storage in subsoils was driven by the redistribution of already stored soil organic matter from the topsoil to deeper soil layers, for example, via bioturbation or dissolved organic matter. Therefore, managing plant diversity may, thus, have significant implications for subsoil carbon storage and other critical ecosystem services.

Plants with arbuscular mycorrhizal fungi efficiently acquire Nitrogen from substrate additions by shaping the decomposer community composition and their net plant carbon demand - Somak Chowdhury; Markus Lange; Ashish A. Malik; Timothy Goodall; Jianbei Huang; Robert I. Griffiths; Gerd Gleixner (Plant and Soil, 2022)
Aims We investigated the role of plants and their plant-derived carbon in shaping the microbial community that decomposes substrates and traced the return of nutrients from decomposition back to plant shoots in order to understand the importance of plants for ecosystem element cycling. Methods We performed a greenhouse experiment having plant communities with and without arbuscular mycorrhizal fungi (AMF) and ingrowth cores that held different 15 N labeled substrates. We determined the microbial community structure using molecular sequencing and the net assimilation of plant carbon into soil microorganisms using a 13 CO 2 pulse and 13 C measurements of microbial biomarkers. We determined the return of nitrogen back to the shoots using the 15 N signal, which was provided from the decomposition of the substrate added to the ingrowth cores. Results We observed that the microbial community composition in the ingrowth cores and their net 13 C assimilation depended on the presence of AMF and the added substrate. Both plant communities had similar 15 N uptake into their shoots, but the net N uptake cost was significantly lower in presence of AMF. In the presence of AMF also lower net N uptake cost was observed for the decomposition of plant-derived and microorganism-derived substrates compared to inorganic nitrogen suggesting that AMF actively controls the decomposer comunity and their carbon demand. Conclusion Our results identify for the first time a functional overlap of soil microorganisms as identical substrate is decomposed by different microorganisms suggesting functional redundancy of microbial communities. In consequence a better understanding of ecosystem element cycling can only be achieved when the whole plant-microorganism-organic matter-soil continuum is investigated.

Drought and recovery effects on belowground respiration dynamics and the partitioning of recent carbon in managed and abandoned grassland - Johannes Ingrisch; Stefan Karlowsky; Roland Hasibeder; Gerd Gleixner; Michael Bahn (Global Change Biology, 2020)
The supply of soil respiration with recent photoassimilates is an important and fast pathway for respiratory loss of carbon (C). To date it is unknown how drought and land‐use change interactively influence the dynamics of recent C in soil‐respired CO 2 . In an in situ common‐garden experiment, we exposed soil‐vegetation monoliths from a managed and a nearby abandoned mountain grassland to an experimental drought. Based on two 13 CO 2 pulse‐labelling campaigns, we traced recently assimilated C in soil respiration during drought, rewetting and early recovery. Independent of grassland management, drought reduced the absolute allocation of recent C to soil respiration. Rewetting triggered a respiration pulse, which was strongly fuelled by C assimilated during drought. In comparison to the managed grassland, the abandoned grassland partitioned more recent C to belowground respiration than to root C storage under ample water supply. Interestingly, this pattern was reversed under drought. We suggest that these different response patterns reflect strategies of the managed and the abandoned grassland to enhance their respective resilience to drought, by fostering their resistance and recovery respectively. We conclude that while severe drought can override the effects of abandonment of grassland management on the respiratory dynamics of recent C, abandonment alters strategies of belowground assimilate investment, with consequences for soil‐CO 2 fluxes during drought and drought‐recovery.

Reconstruction of the Late Holocene climate and environmental history from North Bolgoda Lake, Sri Lanka, using lipid biomarkers and pollen records - Kasun Gayantha; Joyanto Routh; Krishnamurthy Anupama; Jean Lazar; Srinivasan Prasad; Rohana Chandrajith; Patrick Roberts; Gerd Gleixner (Journal of Quaternary Science, 2020)
The catastrophic impact and unpredictability of the Indian Ocean Monsoon (IOM) over South Asia are evident from devastating floods, mudslides and droughts in one of the most densely populated regions of the globe. However, our understanding as to how the IOM has varied in the past, as well as its impact on local environments, remains limited. This is particularly the case for Sri Lanka, where erosional landscapes have limited the availability of well‐stratified, high‐resolution terrestrial archives. Here, we present novel data from an undisturbed sediment core retrieved from the coastal Bolgoda Lake. This includes the presentation of a revised Late Holocene age model as well as an innovative combination of pollen, source‐specific biomarkers, and compound‐specific stable carbon isotopes of n‐ alkanes to reconstruct the shifts in precipitation, salinity and vegetation cover. Our record documents variable climate between 3000 years and the present, with arid conditions c. 2334 and 2067 cal a bp. This extreme dry period was preceded and followed by more wet conditions. The high‐resolution palaeoenvironmental reconstruction fills a major gap in our knowledge on the ramifications of IOM shifts across South Asia and provides insights during a time of major redistribution of dense human settlements across Sri Lanka.

Land Use Alters the Drought Responses of Productivity and CO2 Fluxes in Mountain Grassland - Johannes Ingrisch; Stefan Karlowsky; Alba Anadon-Rosell; Roland Hasibeder; Alexander König; Angela Augusti; Gerd Gleixner; Michael Bahn (Ecosystems, 2018)

Root chemistry and soil fauna, but not soil abiotic conditions explain the effects of plant diversity on root decomposition - Hongmei Chen; Natalie J. Oram; Kathryn E. Barry; Liesje Mommer; Jasper van Ruijven; Hans de Kroon; Anne Ebeling; Nico Eisenhauer; Christine Fischer; Gerd Gleixner; Arthur Gessler; Odette González Macé; et al. (Oecologia, 2017)

Late quaternary hydrological changes at Tangra Yumco, Tibetan Plateau: a compound-specific isotope-based quantification of lake level changes - Franziska Günther; Andrej Thiele; Sophie Biskop; Roland Mäusbacher; Torsten Haberzettl; Tandong Yao; Gerd Gleixner (Journal of Paleolimnology, 2016)

Biogeochemical evidence for freshwater periods during the Last Glacial Maximum recorded in lake sediments from Nam Co, south-central Tibetan Plateau - Roman Witt; Franziska Günther; Stefan Lauterbach; Thomas Kasper; Roland Mäusbacher; Tandong Yao; Gerd Gleixner (Journal of Paleolimnology, 2016)

Plant species diversity affects infiltration capacity in an experimental grassland through changes in soil properties - Christine Fischer; Jana Tischer; Christiane Roscher; Nico Eisenhauer; Janneke Ravenek; Gerd Gleixner; Sabine Attinger; Britta Jensen; Hans de Kroon; Liesje Mommer; Stefan Scheu; Anke Hildebrandt (Plant and Soil, 2015)

Plant diversity shapes microbe‐rhizosphere effects on P mobilisation from organic matter in soil - Nina Hacker; Anne Ebeling; Arthur Gessler; Gerd Gleixner; Odette González Macé; Hans de Kroon; Markus Lange; Liesje Mommer; Nico Eisenhauer; Janneke Ravenek; Stefan Scheu; Alexandra Weigelt; et al. (Ecology Letters, 2015)
Plant species richness ( PSR ) increases nutrient uptake which depletes bioavailable nutrient pools in soil. No such relationship between plant uptake and availability in soil was found for phosphorus (P). We explored PSR effects on P mobilisation [phosphatase activity ( PA )] in soil. PA increased with PSR . The positive PSR effect was not solely due to an increase in C org concentrations because PSR remained significant if related to PA :C org . An increase in PA per unit C org increases the probability of the temporal and spatial match between substrate, enzyme and microorganism potentially serving as an adaption to competition. Carbon use efficiency of microorganisms (C mic :C org ) increased with increasing PSR while enzyme exudation efficiency ( PA :C mic ) remained constant. These findings suggest the need for efficient C rather than P cycling underlying the relationship between PSR and PA . Our results indicate that the coupling between C and P cycling in soil becomes tighter with increasing PSR .

Do n -alkane biomarkers in soils/sediments reflect the δ 2 H isotopic composition of precipitation? A case study from Mt. Kilimanjaro and implications for paleoaltimetry and paleoclimate research - Michael Zech; Roland Zech; Kazimierz Rozanski; Gerd Gleixner; Wolfgang Zech (Isotopes in Environmental and Health Studies, 2015)

Special Issue dedicated to Professor Hanns-Ludwig Schmidt on the occasion of his 85th birthday - Roland A. Werner; Andreas Roßmann; Gerd Gleixner; Christine Lehn; Cornelia C. Metges; Hans Schnyder (Isotopes in Environmental and Health Studies, 2015)

Carbon sequestration potential of hydrothermal carbonization char (hydrochar) in two contrasting soils; results of a 1-year field study - Saadatullah Malghani; Elisabeth Jüschke; Julia Baumert; Angelika Thuille; Markus Antonietti; Susan Trumbore; Gerd Gleixner (Biology and Fertility of Soils, 2015)

Functional diversity of leaf nitrogen concentrations drives grassland carbon fluxes - Alexandru Milcu; Christiane Roscher; Arthur Gessler; Dörte Bachmann; Annette Gockele; Markus Guderle; Damien Landais; Clément Piel; Christophe Escape; Sebastien Devidal; Olivier Ravel; Nina Buchmann; et al. (Ecology Letters, 2014)
Little is known about the role of plant functional diversity for ecosystem‐level carbon (C) fluxes. To fill this knowledge gap, we translocated monoliths hosting communities with four and 16 sown species from a long‐term grassland biodiversity experiment (‘The Jena Experiment’) into a controlled environment facility for ecosystem research (Ecotron). This allowed quantifying the effects of plant diversity on ecosystem C fluxes as well as three parameters of C uptake efficiency (water and nitrogen use efficiencies and apparent quantum yield). By combining data on ecosystem C fluxes with vegetation structure and functional trait‐based predictors, we found that increasing plant species and functional diversity led to higher gross and net ecosystem C uptake rates. Path analyses and light response curves unravelled the diversity of leaf nitrogen concentration in the canopy as a key functional predictor of C fluxes, either directly or indirectly via LAI and aboveground biomass.

Unexpected control of soil carbon turnover by soil carbon concentration - Axel Don; Christian Rödenbeck; Gerd Gleixner (Environmental Chemistry Letters, 2013)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Plant diversity positively affects short‐term soil carbon storage in experimental grasslands - SIBYLLE STEINBEISS; HOLGER BEßLER; CHRISTOF ENGELS; VICKY M. TEMPERTON; NINA BUCHMANN; CHRISTIANE ROSCHER; YVONNE KREUTZIGER; JUSSI BAADE; MAIKE HABEKOST; GERD GLEIXNER (Global Change Biology, 2008)
Increasing atmospheric CO 2 concentration and related climate change have stimulated much interest in the potential of soils to sequester carbon. In ‘The Jena Experiment’, a managed grassland experiment on a former agricultural field, we investigated the link between plant diversity and soil carbon storage. The biodiversity gradient ranged from one to 60 species belonging to four functional groups. Stratified soil samples were taken to 30 cm depth from 86 plots in 2002, 2004 and 2006, and organic carbon contents were determined. Soil organic carbon stocks in 0–30 cm decreased from 7.3 kg C m −2 in 2002 to 6.9 kg C m −2 in 2004, but had recovered to 7.8 kg C m −2 by 2006. During the first 2 years, carbon storage was limited to the top 5 cm of soil while below 10 cm depth, carbon was lost probably as short‐term effect of the land use change. After 4 years, carbon stocks significantly increased within the top 20 cm. More importantly, carbon storage significantly increased with sown species richness (log‐transformed) in all depth segments and even carbon losses were significantly smaller with higher species richness. Although increasing species diversity increased root biomass production, statistical analyses revealed that species diversity per se was more important than biomass production for changes in soil carbon. Below 20 cm depth, the presence of one functional group, tall herbs, significantly reduced carbon losses in the beginning of the experiment. Our analysis indicates that plant species richness and certain plant functional traits accelerate the build‐up of new carbon pools within 4 years. Additionally, higher plant diversity mitigated soil carbon losses in deeper horizons. This suggests that higher biodiversity might lead to higher soil carbon sequestration in the long‐term and therefore the conservation of biodiversity might play a role in greenhouse gas mitigation.

Tracking carbon flow in a 2‐week‐old and 6‐week‐old stream biofilm food web - Clemens Augspurger; Gerd Gleixner; Christiane Kramer; Kirsten KÜsel (Limnology and Oceanography, 2008)
We studied the carbon flow of an allochthonous carbon source (sucrose) in a biofilm food web using stable isotope analysis and lipid biomarkers. Initial biofilms were grown for 2 weeks in a third order stream in Thuringia, Germany, and then incubated in replicate flow channels in climate‐controlled chambers. Either of two sucrose types, differing in their δ 13 C values, was added either immediately (2‐week‐old biofilm) or after a preincubation of 4 weeks (6‐week‐old biofilm). Although sucrose decrease rates were similar with both biofilms, 2‐week‐old biofilms showed a higher carbon uptake capacity cell −1 . The 2‐week‐old biofilm was characterized by low abundances of all trophic levels, which increased one to two orders of magnitude during sucrose consumption. The 6‐week‐old biofilm had higher abundances. Biofilm bacteria incorporated added sucrose carbon, but algae showed no significant carbon incorporation, although a part of this carbon should be mineralized to carbon dioxide by bacteria. Sucrose carbon was also incorporated into ciliates and possibly other protozoans. Grazing rates indicated that up to 23.3% of the sucrose carbon reached higher trophic levels in 2‐week‐old biofilms. Less sucrose carbon was transferred to higher trophic levels in 6‐week‐old biofilms, where similar carbon amounts might have been channelled via filter feeding from the water column to ciliates. Ciliate community composition seemed to be affected by highly abundant rotifers. Whereas total carbon flow in 2‐week‐old biofilms was controlled by bacteria capable of high carbon uptake rates, higher trophic levels were more important in 6‐week‐old biofilms.

A proteomic fingerprint of dissolved organic carbon and of soil particles - Waltraud X. Schulze; Gerd Gleixner; Klaus Kaiser; Georg Guggenberger; Matthias Mann; Ernst-Detlef Schulze (Oecologia, 2005)

Reconstruction of palaeohydrological conditions in a lagoon during the 2nd Zechstein cycle through simultaneous use of ?D values of individual n-alkanes and ?18O and ?13C values of carbonates - Dirk Sachse; Jens Radke; Reinhard Gaupp; Lorenz Schwark; Guido Lniger; Gerd Gleixner (International Journal of Earth Sciences, 2004)

Microbial characteristics of soils on a latitudinal transect in Siberia - HANA ŠANTRU˚CˇKOVÁ; MICHAEL I. BIRD; YEVGENIY N. KALASCHNIKOV; MILAN GRUND; DANA ELHOTTOVÁ; MILOSLAV ŠIMEK; SERGEY GRIGORYEV; GERD GLEIXNER; ALMUT ARNETH; ERNST‐DETLEF SCHULZE; JON LLOYD (Global Change Biology, 2003)
Soil microbial properties were studied from localities on a transect along the Yenisei River, Central Siberia. The 1000 km‐long transect, from 56°N to 68°N, passed through tundra, taiga and pine forest characteristic of Northern Russia. Soil microbial properties were characterized by dehydrogenase activity, microbial biomass, composition of microbial community (PLFAs), respiration rates, denitrification and N mineralization rates. Relationships between vegetation, latitude, soil quality (pH, texture), soil organic carbon (SOC) and the microbial properties were examined using multivariate analysis. In addition, the temperature responses of microbial growth (net growth rate) and activity (soil respiration rate) were tested by laboratory experiments. The major conclusions of the study are as follows: 1. Multivariate analysis of the data revealed significant differences in microbial activity. SOC clay content was positively related to clay content. Soil texture and SOC exhibited the dominant effect on soil microbial parameters, while the vegetation and climatic effects (expressed as a function of latitude) were weaker but still significant. The effect of vegetation cover is linked to SOC quality, which can control soil microbial activity. 2. When compared to fine‐textured soils, coarse‐textured soils have (i) proportionally more SOC bound in microbial biomass, which might result in higher susceptibility of SOC transformation to fluctuation of environmental factors, and (ii) low mineralization potential, but with a substantial part of the consumed C being transformed to microbial products. 3. The soil microbial community from the northernmost study region located within the permafrost zone appears to be adapted to cold conditions. As a result, microbial net growth rate became negative when temperature rose above 5 °C and C mineralization then exceeded C accumulation.

Stable isotope distribution in the major metabolites of source and sink organs of Solanum tuberosum L.: a powerful tool in the study of metabolic partitioning in intact plants - Gerd Gleixner; Charles Scrimgeour; Hanns-Ludwig Schmidt; Roberto Viola (Planta, 1998)